CT-guided radiofrequency ablation of osteoid osteoma: correlation of clinical outcome and imaging features - Rehnitz, Christoph; Sprengel, Simon David; Lehner, Burkhard; Ludwig, Karl; Omlor, Georg; Merle, Christian; Kauczor, Hans-Ulrich; Ewerbeck, Volker; Weber, Marc-André (Diagnostic and interventional radiology, 2013)
The long-term outcome of CT-guided RFA of osteoid osteoma is excellent and the treatment decisions should not be solely based on the imaging findings, but investigators should also be aware of the variety of imaging patterns after RFA. PURPOSE - We aimed to retrospectively evaluate the computed tomography (CT) and magnetic resonance imaging (MRI) findings of patients with osteoid osteoma treated with CT-guided radiofrequency ablation (RFA) along with the clinical outcome and long-term success. MATERIALS AND METHODS - Seventy-three CT-guided RFA procedures were performed in 72 patients. The long-term success was assessed using a questionnaire including several visual analog scale scores. The CT evaluation included pre- and immediate postprocedural imaging of all 72 patients, and MRI was performed in 18 patients with follow-up imaging (mean, 3.4±2.2 months). The evaluation criteria included nidus morphology and a correlation with markers of clinical success. RESULTS - The primary technique effectiveness rate was 71/72 (99%). One relapse was successfully retreated, leading to a secondary technique effectiveness rate of 72/72 (100%). The long-term follow-up (mean, 51.2±31.2 months; range, 3-109 months) revealed a highly significant reduction of all assessed limitation scores (P < 0.001). The CT morphology was typical in all cases and did not change during the short-term follow-up. The follow-up MRI patterns varied considerably, including persistent nidus contrast enhancement in one-third (6/18) and persistent marrow edema in half (9/18) of the patients. None of the investigated MRI and CT patterns correlated with the clinical outcome. CONCLUSION - The long-term outcome of CT-guided RFA of osteoid osteoma is excellent. There is no correlation of the CT and MRI patterns with the clinical outcome. Thus, the treatment decisions should not be solely based on the imaging findings. Investigators should also be aware of the variety of imaging patterns after RFA.
Published: 03 September 2019
Gesehen am 20.12.2021